The Evaluation of an English Preparatory Program Using CIPP Model and Exploring A1 Level Students’ Motivational Beliefs - Görkem Erdogan; Mede, Enisa (Journal of Education and Educational Development, 2021)
The purpose of the present study is to evaluate English Preparatory School Language Program in a state university from students’ and instructors’ point of view and also investigate the students’ motivational beliefs for learning in the existing program. More specifically, Stufflebeam’s (1971) CIPP (context, input, process, product) evaluation model was used to evaluate the English language program whereas MSLQ (motivated strategies for learning questionnaire) developed by Pintrich, Garcia, Mckeachie and Smith (1991) was administered to investigate the motivational beliefs for learning of the participating students. Both quantitative and qualitative data were collected in this study. The quantitative data were obtained through questionnaires administered to 54 Turkish EFL students and 33 EFL instructors enrolled in the A1 (elementary level) English preparatory program. The qualitative data were gathered via semi-structured interviews with 10 students and 5 instructors from the same program. The findings of the study revealed that the program partially succeeded its objectives. Both students and instructors were content with materials, assessment dimensions of the program as well as the teaching methods. On the other hand, there was a need for the improvement of the speaking and listening skills and tasks in the A1 program. In addition to this, among the motivational beliefs of the students, control beliefs, task value and intrinsic goal orientation were perceived to be crucial for the students during the process of English learning. The study provides suggestions and pedagogical implications for the English preparatory programs.
Keywords: English Preparatory Program Evaluation, CIPP Evaluation Model, English Language Teaching and Learning, Foreign Language, Motivational Beliefs